2018
DOI: 10.1596/29327
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Republic of Congo Jobs Diagnostic

Abstract: Some rights reserved This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgment on the part of Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Unlike the 2004 and 2012 surveys which were based on data from the supply side of the labour market, studies which also included data from the demand side found additional causes of unemployment in the DRC: hiring requirements, the types of employers, and the poor business climate. Especially among private employers hiring requirements such as professional experience, language skills, and outstanding labour skills often seemed difficult to meet by both newly graduated persons and long-term jobseekers (Aterido et al 2017). The limitation of job creation due to the weak business climate closed the window of opportunity for many jobseekers (Sumata 2020).…”
Section: Unemployment and Underemploymentmentioning
confidence: 99%
“…Unlike the 2004 and 2012 surveys which were based on data from the supply side of the labour market, studies which also included data from the demand side found additional causes of unemployment in the DRC: hiring requirements, the types of employers, and the poor business climate. Especially among private employers hiring requirements such as professional experience, language skills, and outstanding labour skills often seemed difficult to meet by both newly graduated persons and long-term jobseekers (Aterido et al 2017). The limitation of job creation due to the weak business climate closed the window of opportunity for many jobseekers (Sumata 2020).…”
Section: Unemployment and Underemploymentmentioning
confidence: 99%
“…Yet, Burkina Faso's impressively high labor force participation rate and low unemployment masks sizable shares of working poor, high rates of underemployment, and the challenges the economy faces in providing better jobs (Weber, 2018). Underemployment appears to be an important challenge in DRC more than unemployment (Aterido et al, 2017). While unemployment tends to be a predominantly urban phenomenon, underemployment is rampant in rural areas in DRC and Burkina Faso.…”
Section: Box 6: Benchmarking Key Labor Market Statisticsmentioning
confidence: 99%
“…Low skilled individuals escape unemployment in informal sector, while most high skilled ones often prefer to stay unemployed until they find a formal job. This is stated by Reyes et al (2017), skilled individuals could have the ability to sustain a longer job search to find a more suitable match. Indeed, those with higher education typically have the economic backing from their families to engage in a longer job search.…”
Section: Introductionmentioning
confidence: 99%